2019
DOI: 10.3766/jaaa.18052
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Electrically Evoked Compound Action Potential (ECAP) Measurements in Traditional and Hearing Preservation Cochlear Implantation

Abstract: In current practice, the status of residual low-frequency acoustic hearing in hearing preservation cochlear implantation (CI) is unknown until activation two to three weeks postoperatively. The intraoperatively measured electrically evoked compound action potential (ECAP), a synchronous response from electrically stimulated auditory nerve fibers, is one of the first markers of auditory nerve function after cochlear implant surgery and such may provide information regarding the status of residual low-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…Thus, it seems that these eCAP metrics cannot be used to predict the success of hearing preservation surgery. This finding is in contrast with the findings of a recent study, showing that recipients with successful hearing preservation had larger eCAP maximum amplitudes and lower eCAP thresholds (all three CI manufacturers were represented) (21). This discrepancy may be related to how hearing preservation was defined.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, it seems that these eCAP metrics cannot be used to predict the success of hearing preservation surgery. This finding is in contrast with the findings of a recent study, showing that recipients with successful hearing preservation had larger eCAP maximum amplitudes and lower eCAP thresholds (all three CI manufacturers were represented) (21). This discrepancy may be related to how hearing preservation was defined.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study followed the criteria suggested by the American Academy of Otolaryngology–Head and Neck Surgery (22), that is, LFPTA ≤80 dB HL, whereas Nassiri and colleagues (21) defined hearing preservation as a threshold of ≤90 dB HL at 250 Hz only. Another key distinction between these two reports is that the present study only focused on recipients who were hearing preservation candidates, whereas the study by Nassiri and colleagues (21) also included traditional CI candidates in their sample, who, by virtue of their greater degree of preoperative low-frequency hearing loss, are more likely to have poorer neural survival at the cochlear apex (although their findings remained when comparing only the two groups with preoperative residual hearing). Short-term loss of residual hearing is thought to be a result of mechanical trauma from insertion of the electrode array, which is followed by an inflammatory response (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are layers of complexity to each step of this process that necessitate discussion. From a clinical perspective, it is a risk to initiate treatment on subjects who have any residual cochlear function because the cochlear cells are particularly sensitive to changes within the local environment [96,97]. Thus, many subjects with acquired forms of otologic insult and some remaining natural hearing are unlikely to be candidates in clinical trials for the initiation of targeted treatments [98].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Nassiri et al (2019) showed significant differences in ECAP measures in a large number of CI recipients with and without residual hearing. Residual hearing was defined as unaided air conduction threshold ≤90 dB HL at 250 Hz at CI activation.…”
Section: Introductionmentioning
confidence: 95%